Green extraction techniques of bioactive components from cocoa shell - Pavlović, Nika (Array, 2019)
The aim of this study was to demonstrate that certain types of extraction techniques can give extracts with various bioactive components in different concentrations. Four green extraction techniques were used in this study: supercritical CO2extraction, ultrasound-assisted extraction, cold atmospheric plasma extraction and extraction using deep eutectic solvents. Those modern techniques gave better yields of bioactive components and showed better antioxidant activity of obtained extracts than classical Soxhlet extraction. The bioactive components in obtained extracts were quantified by High Performance Liquid Chromatography. Supercritical CO2extraction gave the highest yields for theobromine content, while ultrasound-assisted extraction with 50% aqueous ethanol solution gave the highest caffeine yields during 30 min of extraction, 35 Hz and 60 °C. The extraction with deep eutectic solvent mixture of choline chloride: oxalic acid and 50% pure H2O at room temperature during 180 min of extraction time gave the highest total phenol content while the same mixture under the same conditions, but during longer extraction time (360 min), gave the highest antioxidant activity. Cocoa shell (CS), due to its nutritional value and bioactive components, has a potential to become a desirable raw material in a large spectrum of functional and pharmaceutical products.